Wednesday

July 23, 2014

July 23, 2014

Posted by **Anonymous** on Sunday, March 31, 2013 at 9:25am.

r*n∁r=n*(n-1)∁(r-1)

**Related Questions**

maths - If the sum of the squares of the roots of the quadratic equation ax^2 + ...

Advanced Maths (Vectors) AQA Level - Triangle ABC with D, E and F the midpoints ...

Advanced Maths (Vectors) AQA Level - Triangle ABC with D, E and F the midpoints ...

DISCRETE MATHS - Prove that for every set S, Ø \subseteq( S. i need to Use ...

Maths - X and Y are points on the sides BC and AC of a triangle ABC respectively...

Maths - prove that 2+2=5

maths - prove that: 1/1+x^b-a + x^c-a + 1/1+x^a-b +x^a-c = 1

maths - prove that : 2^n + 2^n-1 / 2^n+1 - 2^n = 3/2

maths - If a+b+c=0 then prove that a^4+b^4+c^4=2(a^2b^2+b^2c^2+c^2a^2)

maths - prove that 2 2 2 2 (n-1) + n + (n+1) = 3n +2